ISOLATION AND PROFILLING OVIDUCT SPECIFICT GLYCOPROTEIN IN OVIDUCTAL FLUID OF KACANG GOAT (Capra aegagrus hircus) - Herlina Pratiwi (Journal of Environmental Engineering and Sustainable Technology, 2017)
Frozen semen supplemented by Oviduct Specific Glycoprotein (OVGP) is a new way to solve the decrease of in vitro fertility on goats caused by polyspermy and to increase the efficiency of artificial insemination on goats. Oviduct Specific Glycoprotein has associated with zona pellucida and localized in perivitelline space. The existence of Oviduct Specific Glycoprotein in perivitelline space may be linked to a mechanism that blocks polyspermic through vitelin block. Oviduct Specific Glycoprotein can be found in the fluid that was secreted by the oviduct (oviductal fluid). This study was aimed to determine Oviduct Specific Glycoprotein profile in the oviductal fluid of Kacang goats Malang district, West Java Province, Indonesia. Oviduct Specific Glycoproteins were collected from an oviductal liquid of kacang goats and samples were loaded to 12% SDS-PAGE to determine the weight of the molecule of Oviduct Specific Glycoprotein, further confirmed by western blot. The result of this study showed that molecule weight of Oviduct Specific Glycoprotein been collected from oviductal liquid was approximately 55-65 kDa. After being confirmed by western blotting the molecule weight of Oviduct Specific Glycoprotein was 65 kDa.